Fetal Intraventricular Hemorrhage Due to Antiphospholipid Syndrome: A Case Report - Bouw, M. C.; Nij Bijvank, S. W. A.; Bouwhuis, J. W.; Wezel-Meijler, G. van (Frontiers in Pediatrics, 2021)
Obstetric Antiphospholipid Syndrome (OAPS) is an autoimmune disease characterized by certain pregnancy complications in association with persistent antiphospholipid antibodies. These antibodies are generally known for their prothrombotic characteristics and may affect mother and fetus during the entire pregnancy. The clinical criteria for OAPS, including recurrent fetal loss, intra-uterine growth restriction and premature birth due to severe preeclampsia, all suggest uteroplacental vascular insufficiency. Although rare, thrombotic complications have been described in neonates born to mothers with OAPS, mainly ischemic stroke. We report on the first case of extensive fetal intraventricular hemorrhage related to OAPS. We share our diagnostic search and analysis for this unusual antenatal event, including cranial ultrasound findings and postmortem MRI images. We will also present a short review of the etiology and prognosis of antenatal intraventricular hemorrhage. We suggest that women with severe or early preeclampsia and/or a history of pregnancy loss should be evaluated for OAPS and carefully monitored throughout pregnancy. Further, we advise to test mothers for OAPS in the case of idiopathic fetal hemorrhage.